Kagan, Donald; Kagan, Frederick W., 1970- - 355.033573 (New York St. Martin's Press, 2000)
Traces Britain's international and defense policies in the years between World War I and II and studies the how their self-delusion and unwillingness to face their responsibilities affected the world at the start of World War II.
Include Notes, Bibliography, Index and Maps.
Keywords: Military Policy -- United States -- Great Britain